SAT0382 Palace 4, A Phase 3, Randomized, Controlled TRIAL of Apremilast, an Oral Phosphodiesterase 4 Inhibitor, for Treatment of Psoriatic Arthritis: Long-Term (52-WEEK) Improvements in Physical Function. (10th June 2014) - Wells, A.; Edwards, C.; Adebajo, A.O.; Kivitz, A.J.; Bird, P.; Shah, K.; Hu, C.; Stevens, R.M.; Aelion, J.A.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to regulate inflammatory mediators. PALACE 4 compared APR efficacy/safety with placebo (PBO) in patients (pts) with active PsA who were DMARD-naïve. Objectives: Evaluate the impact of APR over 52 wks on physical function among PALACE 4 pts. Methods: Pts were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30). Pts with <20% reduction from BL in SJC or TJC at Wk 16 were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on the initial APR dose. At Wk 24, all remaining PBO pts were re-randomized to APR20 or APR30. This analysis reports data for Wks 0-52. Physical function was evaluated using HAQ-DI and SF-36v2 Physical Function (PF) domain and physical component summary (PCS) scores. Proportions of pts initially randomized to APR achieving minimum clinically important difference (MCID) thresholds at Wk 52 for HAQ-DI (≥0.13 or ≥0.30) 1, 2 and SF-36v2 PF and PCS (both ≥2.5) 3 were determined. Results: At Wk 16, a significantly greater proportion of pts treated with APR achieved a modified ACR20 response vs PBO (primary endpoint). Mean changes in HAQ-DI at Wk 16 (key secondary endpoint) were 0.03 (PBO), -0.17 (APR20; P =0.0008), and -0.21 (APR30; P <0.0001). Among pts who were treated with APR continuously through 52 wks, sustained improvement in HAQ-DI was observed. Mean change in HAQ-DI was -0.32 (APR20) and -0.39 (APR30) at Wk 52, exceeding MCID thresholds of ≥0.13 or ≥0.30 (Table). At Wk 52, 56.8% (APR20) and 59.0% (APR30) achieved HAQ-DI MCID ≥-0.13 and 48.5% and 48.9% achieved MCID ≥-0.30, respectively. Wk 52 mean changes from BL in SF-36v2 PF (APR20, 4.61; APR30, 6.41) and PCS (APR20, 5.55; APR30, 6.67) exceeded the MCID threshold (≥2.5). At Wk 52, 57.6% of APR20 and APR30 pts achieved SF-36v2 PF MCID, and 60.6% (APR20) and 69.1% (APR30) achieved SF-36v2 PCS MCID. The most common AEs reported during the PBO-controlled period were nausea (12.6%), diarrhea (9.4%), and headache (6.0%). The safety profile of APR for up to 52 wks was similar to that observed with APR for up to 24 wks of treatment (PBO-controlled period). Conclusions: Over 52 wks, APR continued to demonstrate clinically meaningful improvements in physical function in active PsA pts who were DMARD-naive. APR demonstrated an acceptable safety profile and was generally well tolerated for up to 52 wks. References: Kwok T. J Rheumatol. 2010;37:1024. Mease PJ. J Rheumatol. 2011;38:2461. Revicki DA. Health Qual Life Outcomes. 2008;6:75. Disclosure of Interest: A. Wells Grant/research support: Celgene Corporation, C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Consultant for: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, A. Adebajo: None declared, A. Kivitz Grant/research support: Amgen, Janssen, Eli Lilly, Novartis, Pfizer Inc, and UCB, Consultant for: Amgen, Janssen, Eli Lilly, Novartis, Pfizer Inc, and UCB, Speakers bureau: Pfizer Inc, P. Bird Grant/research support: Celgene Corporation, K. Shah Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, J. Aelion Grant/research support: Ardea, Astra Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor, Galapagos, Genentech, GlaxoSmithKline, Human Genome Sciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer Inc, Roche, UCB Biosciences, Sanofi-Aventis, Takeda, and Vertex, Consultant for: Ardea, Astra Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor, Galapagos, Genentech, GlaxoSmithKline, Human Genome Sciences, Janssen, Eli Lilly, Merck, Mesoblast, Novartis, Novo Nordisk, Pfizer Inc, Roche, UCB Biosciences, Sanofi-Aventis, Takeda, and Vertex, Speakers bureau: AbbVie, Amgen, and UCB DOI: 10.1136/annrheumdis-2014-eular.1096